Analisis Implementasi Google Drive Terhadap Produktivitas Operasional Excisia Photography - Fendy Bayu Firmansyah; Imam Thoib; Nafis Sururi; Beda Puspita; Danang Satya Nugraha; Nicky Dwi Kurnia (LKP KARYA PRIMA KURSUS, 2026)
Excisia Photography, a professional photography service business in Kediri City, faced various operational obstacles hindering productivity, including slow file delivery to clients, difficulty in team coordination for file sharing, risk of data loss due to reliance on physical storage media, and inefficient manual archiving systems. This study aims to analyze the effect of Google Drive implementation as a cloud storage solution on the operational productivity of Excisia Photography, encompassing aspects of file distribution speed, team collaboration ease, data storage security, and work time efficiency. A descriptive quantitative approach was employed using total sampling of five core team members. Data were collected through a Likert-scale questionnaire (1–5) and semi-structured interviews. Results indicate that all productivity indicators achieved very good average scores, with the highest on the file delivery speed dimension (average 4.80), followed by file accessibility, data security, and work efficiency (each 4.60), and team collaboration (4.40). Interview data revealed a 35–40% reduction in project cycle completion time and nearly a twofold increase in production capacity following implementation. It is concluded that Google Drive has a significantly positive effect on the operational productivity of Excisia Photography and can serve as a strategic recommendation for similar photography businesses undergoing digital transformation.